Analysis of Individual Characteristics and Infrastructure of Employee Performance through Job Satisfaction at Tax Management Agency and Regional Retribution (BP2RD) UPT Samsat Medan Utara - Fionita Idanesia Br Tarigan; Endang Sulistya Rini; Ritha F. Dalimunthe (Budapest International Research and Critics University, 2022)
Organizations in this era are required to have advantages both in terms of service, cost, product quality and professional human resources. However, good infrastructure will be useless if human resources do not support it. This means that human resources remain an important factor for advancing the organization. In this case the organization requires quality human resources. Quality human resources are human resources who are able and willing to do things that go beyond the demands of organizational standards. Therefore, good employee behavior is important and should exist in employees because positive actions taken will produce quality and beneficial performance for the organization. Factors that can affect the high involvement of employees and good behavior can be triggered by several aspects such as individual characteristics and infrastructure. This study aims to analyze individual characteristics and infrastructure on employee performance through job satisfaction at the Regional Tax and Retribution Management Agency (BP2RD) UPT Samsat Medan Utara. The objective of the research is to analyze of individual characteristics and infrastructure of employee performance through job satisfaction at the Regional Tax and Levy Management Agency (BP2RD) UPT Samsat Medan Utara. This type of research is causal with a quantitative approach. The population in this study were all employees who worked at the Regional Tax and Retribution Management Agency (BP2RD) UPT Samsat Medan Utara, totaling to 70 employees. Used primary and secondary data which are obtained through documentation study and question list. The data are analyzed with structural equation modeling (SEM) using SmartPLS version 3.0 analysis tool. The results demonstrated that individual characteristic had a positive and significant effect on employee performance, infrastructure positive and significant effect on employee performance, individual characteristic had a positive and significant effect on job satisfaction, infrastructure positive and significant effect on job satisfaction, job satisfaction had positive and significant effect on employee performance. Individual characteristic had an indirect positive and significant effect on employee performance through job satisfaction and infrastructure had a positive and significant effect on employee performance through job satisfaction.